Primary School Students' Knowledge About Menarche and Their Readiness: A Comparative Study - Putra, Kusuma Wijaya Ridi; Fiddaroini, Fakhrun Nisa’; Kurniawan, Vendi Eko (YCAB Publisher, 2025)
Background: Menarche represents a critical developmental milestone in the lives of young girls, often accompanied by a range of emotional responses influenced by the level of knowledge and preparedness. Inadequate preparation and prevalent misconceptions may contribute to heightened anxiety and suboptimal menstrual hygiene practices, particularly in low- and middle-income settings. Objective: This study aimed to compare the levels of knowledge and readiness for menarche among primary school girls residing in two contrasting geographic contexts: a provincial buffer zone and a tourist region. Methods: A comparative research design was utilized, involving a sample of 184 female students from grades 5 and 6 enrolled in schools located in the buffer zone of a provincial capital and in designated tourist areas. Data were collected using structured questionnaires adapted from validated instruments to assess knowledge and readiness for menarche. Spearman's Rho correlation test was applied to analyze the association between knowledge and readiness, while independent samples t-tests were used to compare the mean differences between the two groups. Results: The findings revealed a strong positive correlation between knowledge and readiness in Sidoarjo Regency (r = .788, p < .001) and a moderate positive correlation in Malang City (r = .505, p < .001). Although several students demonstrated adequate knowledge, notable gaps in readiness—particularly in Malang—highlight the influence of additional factors such as socio-cultural norms and the availability of practical support systems. Conclusion: While increasing knowledge about menarche is vital to improving readiness, effective menstrual health management (MHM) necessitates comprehensive educational strategies and the provision of supportive infrastructure. The study underscores the importance of initiating early, culturally responsive menstrual education and ensuring adequate school facilities to foster positive health behaviors and diminish menstrual-related stigma. Keywords: menarche knowledge; menarche readiness; menstrual health management; menstrual education